Fulfilment of the Right to a Fair Justice for Victims and Narcotics Abusers in Indonesia - Putra, I Made Widia Wirya; Sulistianingsih, Dewi; Muhtada, Dani (Universitas Negeri Semarang, 2024)
The purpose of this paper is to analyze the fulfillment of the right to rehabilitation for addicts and victims of narcotics abuse in Indonesia in the perspective of the right to a fair trial. The research method used in normative legal research is because the focus is to study written law from various aspects, such as theory, history, philosophy, structure and composition, scope and material, article by article and general explanation, formality and binding force of a law and the legal language used. The approach used in this study is the approach Statute Approach which is an approach to review legislation related to research themes, Analytical & Conceptual Approach which is an approach by studying views and doctrines that develop in legal science. The mechanism for applying rehabilitation sanctions itself is based on an assessment, assessment is known to be an assessment action to find out the condition of residents due to drug abuse which includes medical aspects and social aspects, this is what must be done by law enforcement officials to guarantee their rights as suspects such as the Justice Fair Trial Principle. The central-level Integrated Assessment Team (TAT) is determined by the National Narcotics Agency (BNN), after coordinating with the Ministry of Health, the National Police, the Indonesian Prosecutor's Office, and the Ministry of Law and Human Rights (BAPAS), related to the application of rehabilitation sanctions against addicts and victims of narcotics abuse, after obtaining approval from each of these agencies.